ANALYTICAL STUDY ON EFFECT OF CENTRAL OPENING OF MASONRY INFILL TO THE LATERAL STRENGTH OF RC FRAME STRUCTURE - Medriosa, Hamdeni; Maidiawati , Maidiawati; Tanjung , Jafril; Zaidir, Zaidir (Journal of Applied Engineering Science, 2022)
In order to get accuration analytical model for describing the lateral strength of brick masonry with openings, a newly simple method was introduced. Comparison of reinforced concrete frame structures with openings and the experimental results of brick masonry with openings (holes) of 25% and 40% was used in this analytical model. In the high-risk seismic areas many reinforced concrete buildings with infill frame with openings. Where the presence of openings will reduce the strength of the wall. In addition, the influence of the area and location openings in the walls are strongly needed to obtain a more realistic method for designing reinforced concrete structures.The brick mansory was assumed as the non-structural component. However, based on the observations after the earthquake, the presence of brick masonry has a significant contribution to the seismic capacity of reinforced concrete structures. The diagonal strut method was used, where the elastic and plastic behavior of the fill-portal by considering the limited ductility of the infill frame material. The comparison of the new analytical model and the experimental brick masonry with opening 25% and brick masonry with opening 40% shows a good agreement. Finally, it can be said that the new analytical model can be used.
Keywords: analytical study, central opening, masonry infill, lateral strength, RC Frame